Rascal a memoir of a better era. - North, Sterling 1906-; Schoenherr, John (New York Dutton, 1963)
The author's carefree life in a small midwestern town at the close of World War I, and his adventures with his pet raccoon, Rascal.
Autobiographical.
Keywords: Raccoons -- Biography; Raccoons; Country life -- Wisconsin